Septuagintas betydning for udfoldelsen af nytestamentlig teologi - Müller, Mogens (Dansk Teologisk Tidsskrift, 2016)
This second part of an article on the significance of the Septuagint for the development of New Testament theology takes up a series of text examples and single terms where the Septuagint version of the Old Testament has influenced the New Testament. One outstanding example in the first category is the concept of virgin birth in Matthew 1,23 that derives from Isaiah 7,14. To the second category belongs not least the Septuagint’s rendering of the tetragram by means of κύριος, Lord, a rendering that also made it applicable to Jesus.